Performance and Optimization of Normal Concrete with Binary Cementitious Blends of Bagasse Ash and Rice Husk Ash - Lase, Firman Kornel; Herwani, Herwani; Mukti, Elsa Tri (Fakultas Teknik Universitas Tanjungpura, 2025)
This study evaluates the use of Bagasse Ash (BA) and Rice Husk Ash (RHA) as partial cement replacements in standard concrete. The experiment used cylindrical specimens with diameters of 10 cm and 15 cm, with cement replaced by BA and RHA at 0% (control), 2.5%+2.5%, 5%+5%, and 7.5%+7.5%. Tests on material properties and concrete performance—including slump, unit weight, compressive strength, and splitting tensile strength—were conducted in accordance with Indonesian National Standards (SNI). The results show that increasing BA and RHA content reduces slump values, from 90 mm in the control mixture to 75 mm at the highest substitution level, but all mixtures remained within the acceptable workability range of 75–100 mm and met the criteria for normal-weight concrete. The highest 28-day compressive strength, 32.900 MPa, was achieved with the 2.5% BA + 2.5% RHA mixture, slightly exceeding that of the control concrete. The greatest splitting tensile strength, 2.924 MPa, occurred at the 5% BA + 5% RHA level. Overall, the findings indicate that moderate substitution using BA and RHA can maintain satisfactory mechanical performance while offering a more sustainable alternative to conventional cement.